Genome-Wide Association Study for Flowering Time in Korean Cowpea Germplasm - Seo, Eunju; Kim, Kipoong; Kang, Ryulyi; Kim, Gyutae; Park, Aron; Kim, Woon Ji; Sun, Hokeun; Ha, Bo-Keun (Plant breeding and biotechnology, 2020)
Cowpea is an annual legume crop; although it is an essential food in developing countries, cowpea is now grownworldwide. For the genetic improvement of plants, flowering time is one of the major selection criteria. In general, flowering isregulated by photoperiod and temperature, along with the interaction between environmental factors. In this study, we aimed toinvestigate the candidate genes associated with flowering time using genome-wide association study (GWAS). To investigate theflowering time-related genes, 384 cowpea germplasms were genotyped with 51,128 single nucleotide polymorphisms (SNPs). Themain genetic component of days to flowering (DTF) was analyzed using genome association and prediction integrated tool (GAPIT)and elastic-net analyses. From the GAPIT and elastic-net analyses, a total of 23 SNPs were significantly associated with DTF amongfive (chr. 2, 3, 7, 9, and 11) and seven different chromosomes (chr. 1, 2, 3, 4, 5, 8, and 9), respectively. Based on our analysis,Vigun01g084000, Vigun01g227200, Vigun02g062600, and Vigun03g296800 were considered the major candidate genes that weresignificantly associated with DTF in cowpea. These results confirmed that DTF might be controlled by multiple genes affecting earlyflowering, delaying flowering time, repressing the transition to flowering, etc. This study will potentially contribute to effective DTFgenomic selection in plant breeding to better understand the genetic basis and explore the mechanism of flowering time. KCI Citation Count: 0